Screening of significant factors affecting pravastatin production by Penicillium sp. ESF21P - Norazwina, Zainol; Seydametova, Emine; Jailani, Salihon; Convey, Peter (Institute of Physics Publishing, 2020)
Pravastatin is a clinically useful cholesterol-lowering agent. The development of a one-step fermentation process using pravastatin-producing microfungi may be an attractive approach from an economic point of view. To facilitate this, previously 54 fungal cultures were isolated from soil samples. Among them, Penicillium sp. ESF21P was the most active pravastatin producer (196.83 mg/L). The objective of the present study is to determine significant factors affecting pravastatin production by Penicillium sp. ESF21P. The method of the 27-3 fractional factorial design with seven variables was performed using Design-Expert 6.0.8 software package. The seven factors studied were slant age, spore concentration, inoculum volume, fermentation time, temperature, initial pH of the medium, and agitation rate. The results obtained confirmed that the factorial model was significant. Amongst the tested factors, only four were important: agitation rate, slant age, initial pH of the medium, and fermentation time with a percentage contribution of 25.66%, 11.56%, 9.72%, and 7.69%, respectively. These significant factors will be optimized further using response surface methodology.